2009
DOI: 10.1364/ao.48.005728
|View full text |Cite
|
Sign up to set email alerts
|

Effects of residue and antioxidant on thermo-optical properties of biodiesel

Abstract: Thermal lens (TL) spectrometry was applied to soybean biodiesel samples, in order to assess the behavior of their thermo-optical properties during the preparation before and after the washing process. The study was based on the thermal diffusivity parameter, which is highly sensitive and is related to the chemical composition of the sample. The results showed a difference of approximately 20% between the initial (unwashed) and the final (washed) steps of biodiesel production. This behavior indicates that the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 9 publications
3
6
0
1
Order By: Relevance
“…The results of thermal conductivity can be determined using the relation  = k/c. The values obtained are in agreement with the results from literature (Castro et al 2005, Lima et al 2009). Several factors, such as presence air, light, heat (high temperature), light traces of metal, antioxidants, peroxides as well as the nature of the storage containers can trigger oxidative processes, thus will be altered the quality of biodiesel (Knothe et al, 2005).…”
Section: Thermal Properties Of Biodiesel Using Thermal Lens and Photosupporting
confidence: 92%
See 2 more Smart Citations
“…The results of thermal conductivity can be determined using the relation  = k/c. The values obtained are in agreement with the results from literature (Castro et al 2005, Lima et al 2009). Several factors, such as presence air, light, heat (high temperature), light traces of metal, antioxidants, peroxides as well as the nature of the storage containers can trigger oxidative processes, thus will be altered the quality of biodiesel (Knothe et al, 2005).…”
Section: Thermal Properties Of Biodiesel Using Thermal Lens and Photosupporting
confidence: 92%
“…This variation may be related to oxidative processes because the thermal diffusivity measurements between the TL and PPE were carried out to set at the intervals of 15 months, approximately. Similar results were observed by Lima et al 2009 andCastro et al, (2005) which observed a reduction in the thermal diffusivities in oxidated samples.…”
Section: Thermal Properties Of Biodiesel Using Thermal Lens and Photosupporting
confidence: 87%
See 1 more Smart Citation
“…A indicação das coroas unitárias totalmente cerâmicas tem como objetivo reabilitar principalmente a estética, autoestima e bem estar além de promover a saúde periodontal, periapical e melhorar a função mastigatória da paciente. Estudos recentes sugerem que a confecção de coroas com sistemas cerâmicos totalmente livres de metal são uma excelente alternativa restauradora, com potencial estético superior ao das coroas metalocerâmicas 2,6,17,19,20 . Vários estudos mostram que a prótese de cerâmica pura é indicada em áreas onde se faz necessária cobertura total e estética máxima, no entanto não é indicada para reabilitação em dentes posteriores devido à maior tensão mastigatória 4,5,8 .…”
Section: Discussionunclassified
“…Thermal lens (TL) spectroscopy has been extensively used to characterize different materials, including solutions such as oil and biodiesel. [13][14][15][16] The TL procedure centers on the observation of the heat generated in the sample when it absorbs energy from a laser beam with a Gaussian intensity profile. The absorbed energy induces a temperature variation in the sample that is larger in the center than at the border of the beam, following the spatial distribution of the laser beam intensity.…”
Section: Introductionmentioning
confidence: 99%